Pengaruh Interval Training dan Cross Country Terhadap VO2max - Tomi Wahyuda; Sudirman Husin; Lungit Wicaksono (JUPE (Jurnal Penjaskesrek), 2018)
The problem in this study is that there are still students who take futsal extracurricular activities at Negeni 6 Bandar Lampung High School experiencing fatigue during the competition, not yet knowing the effect of interval training and cross country on vo2max for students who take futsal extracurricular activities at Bandar Lampung SMA 6. The research objective is to determine whether there is an effect of interval training and cross country on voaxmax for students who take futsal extracurricular activities at Bandar Lampung 6 Public High School. The method used in this study is an experiment. The population of this research was 30 students who participated in futsal extracurricular activities at Bandar Lampung Senior High School 6. Data analysis using t-test. The results showed that there were 4.199 and cross country interval training influences of 2.261 to vo2max and the most influential to vo2max was interval training and the difference in interval training and cross country to vo2max.Masalah dalam penelitian ini adalah masih ada siswa yang mengikuti ekstrakurikuler futsal di SMA Negeri 6 Bandar Lampung mengalami kelelahan saat pertandingan, belum diketahuinya pengaruh interval training dan cross country terhadap vo2max  pada siswa yang mengikuti ekstrakurikuler futsal di SMA Negeri 6 Bandar Lampung. Tujuan penelitian untuk mengetahui apakah ada pengaruh interval training dan cross country terhadap vo2max pada siswa yang mengikuti ekstrakurikuler futsal di SMA Negeri 6 Bandar Lampung. Metode yang digunakan dalam penelitian ini adalah eksperimen. Populasi penelitian ini adalah siswa yang mengikuti ekstrakurikuler futsal di SMA Negeri 6 Bandar Lampung berjumlah 30 orang. Analisis data menggunakan Uji-t. Hasil penelitian menunjukkan ada pengaruh interval training sebesar 4,199 dan cross country sebesar 2,261 terhadap vo2max dan yang paling berpengaruh terhadap vo2max adalah interval training serta adanya perbedaan interval training dan cross country terhadap vo2max.Kata kunci: cross country, interval training, vo2max.